Study on the Yellowing Property of Light-colored Leather for Car Seat Cushion - Xuanxuan YUE; Li LIU; Weidong QIU (Pige Kexue Yu Gongcheng)
Currently, there is a growing application for light-colored leather in the automotive seat cover. However, the tendency of light-colored leather to yellow limits its application. Based on the mechanism of yellowing and influencing factors, this work proposed a set of verification methods and the corresponding requirements for the yellowing of light-colored leather. They mainly included the thermal aging test method for bonded overs, the light aging verification adding specific vehicle window glass, as well as a new and systematic amination dyeing method. Through the practical application, these verification methods can accurately identify the yellowing risk of light-colored leather fabrics in the early stage of design, providing the guidance for their application.